FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBIAYAAN MURABAHAH PADA BANK UMUM SYARIAH DI INDONESIA - Eka Sulistya Rindi, - (2019)
The purpose of this study is to find empirical evidence and analyze the influence of factors that influence murabahah financing in Sharia Commercial Bank in Indonesia on murabahah financing during the period 2013-2017. In this study, the sample consisted of 13 Sharia Commercial Bank analyzed using purposive sampling method. The data that used is a secondary data from the Sharia Commercial Bank Financial Statements from the bank's official website. Hypothesis testing in this study was using multiple regression method and analysed by SPSS25 software with significance level of 5 percent. The result partially showed that BI 7-Day (Reverse) Repo Rate does not significantly impact Murabahah Financing. Financing to Deposit Ratio (FDR) negatively and significantly impacted while Return On Asset (ROA) positively and significantly impacted Murabahah Financing.